The current child and adolescent health screening system: an assessment and proposal for an early and periodic check-up program - Baik-Lin Eun; Jin Soo Moon; So-Hee Eun; Hea Kyoung Lee; Son Moon Shin; In Kyung Sung; Hee Jung Chung (Korean Pediatric Society, 2010)
Purpose : Recent changes in the population structure of Korea, such as rapid decline in birth rate and exponential increase in old-aged people, prompted us to prepare a new health improvement program in children and adolescents. Methods : We reviewed current health screenings applied for children and adolescents in Korea and other developed countries. We collected and reviewed population-based data focused on mortality and morbidity, and other health-related statistical data. We generated problem lists in current systems and developed new principles. Results : Current health screening programs for children and adolescents were usually based on laboratory tests, such as blood tests, urinalysis, and radiologic tests. Almost all of these programs lacked evidence based on population data or controlled studies. In most developed countries, laboratory tests are used only very selectively, and they usually focus on primary prevention of diseases and health improvement using anticipatory guidance. In Korea, statistics on mortality and morbidity reveal that diseases related to lifestyle, such as obesity and metabolic syndrome, are increasing in all generations. Conclusion : We recommend a periodic health screening program with anticipatory guidance, which is focused on growth and developmental surveillance in infants and children. We no longer recommend old programs that are based on laboratory and radiologic examinations. School health screening programs should also be changed to meet current health issues, such as developing a healthier lifestyle to minimize risk behaviors—for example, good mental health, balanced nutrition, and more exercise.